Condition of Coral Reefs at Mentigi Beach, North Lombok Regency - Murdani, Muhammad Taufiq Zulfikri; Candri, Dining Aidil; Ahyadi, Hilman (Jurnal Pijar Mipa, 2025)
Climate change and excessive anthropogenic activities have an impact on coral reef damage. Coral reef damage can be seen from several criteria, one of which is the percentage of live coral cover. North Lombok is one of the districts on Lombok Island whose coral cover has been damaged.  This research aims to identify marine biota, coral reef genus, analyze community structure and condition of coral reefs at Mentigi Beach. Coral reef genus data was taken using Coral Finder 2.0 Indo Pacific by Russel Kelley, while coral reef data was obtained using the UPT (Underwater Photo Transect) method at three stations with depths of 1-5 meters and 6-10 meters. The results showed that live coral cover at stations I, II, and III were 12.44%, 17.42%, and 32.46%, respectively. At a depth of 1-5 meters, it was found to be 21.93%, and 19.62% at a depth of 6-10 meters. There are 11 benthic categories, and 30 coral reef genera identified. The Porites genus is cosmopolitan in the research location. The diversity, evenness and dominance indices show that coral reef genera are evenly distributed with no one dominating the coral reef ecosystem at Mentigi Beach, Pamenang, North Lombok Regency.